PEMANFAATAN TEKNOLOGI QR MONEY DALAM MENINGKATKAN TATA KELOLA USAHA DI BUMDES BINA BERSAMA - Rio Priantama; Tito Sugiharto; Yulyanto (Politeknik Negeri Sriwijaya, 2023)
BUMDes as a supporter of village economic resilience has been rolled out and regulated in various laws and regulations, such as Regulation of the Minister of Villages, Development of Disadvantaged Regions, and Transmigration of the Republic of Indonesia No. 4 of 2015 concerning Establishment, Management and Management, and dissolution of Village-Owned Enterprises and as well as No. 22 of 2015 2016 concerning Priority Setting for the Use of Village Funds for 2017. BUMDes Bina Bersama Desa Bojongnegara has problems one of which is accountability for the management of BUMDes funds. Discrepancies between reports and activity implementation, disbursement of funds that are not supported by evidence, and verification of reports that are not carried out every month, are indications that accountability has not been going well. One alternative solution as an effort to overcome this problem is to utilize QR Money technology in business management at BUMDes Bina Bersama, Bojongnegara Village, Ciledug District, Cirebon Regency. This community service aims to provide an understanding of the use of information technology, especially QR Money as a financial management mechanism for various sources of income. This service activity in the form of mentoring and training obtained measurable results and benefits in the form of the level of understanding of BUMDES administrators and the community about BUMDES Governance Indicators after utilizing QR Money technology in maximizing financial governance and sources of income.